Comparative efficacy of different ultrasound-guided ablation for the treatment of benign thyroid nodules: Systematic review and network meta-analysis of randomized controlled trials. - Linye He; Wanjun Zhao; Zijing Xia; Anping Su; Zhihui Li; Jingqiang Zhu (PLoS ONE)
Background Percutaneous ablation is currently deemed an additionally treatment option for benign thyroid nodules in the world, but possibly different effect among the ablation modalities is not clear. So we aim to evaluate the efficacy and complications of thermal/chemical ablation by network meta-analysis. Materials and methods In the network meta-analysis, PubMed, EMBASE and the Cochrane Library databases were searched from 1980 to 2020. Studies of adults with thyroid benign nodules under percutaneous ablation therapy were included. Percentage mean volume change, symptom score change, cosmetic score change and complications were evaluated by network meta-analysis. Results In the network meta-analysis, Radiofrequency Ablation(RFA) with 2 treatment sessions group was associated with the highest reduction for the mean volume change during 6-month follow-up (MD = 79.09 and 95% CrI:48.23-89.94). There is no significant difference in the incidence of complications. Subgroup analysis showed that 2 sessions of Radiofrequency Ablation (RFA) ranks the highest probability (surface under the cumulative ranking curve (SUCRA) values 77.9) of being the most efficacious treatment for solid or predominantly solid benign nodules. Ethanol ablation (EA) ranked first (SUCRA value 81.1) in the treatment for cyst or predominantly cyst benign nodules. Conclusion RFA appears to be superior to other US-guided percutaneous ablation in reducing benign thyroid nodule volume during short- and long-term follow-up. In the subgroup analysis, RFA with 2 treatment sessions showed the most significant effectiveness for solid benign thyroid nodules and EA showed more effectiveness to decrease the volume of cyst benign thyroid nodules.